(untitled) (International Journal of Engineering and Computer Science, 2016)
In this paper we brainstorm and discuss about different data mining methods that we have effectively connected for digital security. These applications incorporate however are not restricted to pernicious code location by mining double executables, system interruption recognition by mining system movement, peculiarity discovery, and information stream mining. Data mining based interruption location instruments are amazingly valuable in finding security breaks.